Introduction to geophysical fluid dynamics : physical and numerical aspects - Cushman-Roisin, Benoit, 1954- (International geophysics series ;, 2011)
This book provides an introductory-level exploration of geophysical fluid dynamics (GFD), the principles governing air and water flows on large terrestrial scales. Physical principles are illustrated with the aid of the simplest existing models, and the computer methods are shown in juxtaposition with the equations to which they apply. It explores contemporary topics of climate dynamics and equatorial dynamics including the Greenhouse Effect, global warming, and the El Niño Southern Oscillation. Combines both physical and numerical aspects of geophysical fluid dynamics into a single affordable volume Explores contemporary topics such as the Greenhouse Effect, global warming and the El Niño Southern Oscillation Biographical and historical notes at the ends of chapters trace the intellectual development of the field Recipient of the 2010 Wernaers Prize, awarded each year by the National Fund for Scientific Research of Belgium (FNR-FNRS).